Interacciones sociales en el valle de Huarmey, durante el intermedio tardío: Análisis estructural, tecnológico y estilístico de los textiles Casma del Complejo Arqueológico El Campanario, Huarmey – Ancash. - Fernandez Siccha, Diego Leandro (2019)
This research is responsible for conducting studies on textiles. Casma of the Archaeological Complex, through a structural, technological and stylistic analysis, with the purpose of gathering information that allows knowing and interpreting the social interactions that maintain the Casma de Huarmey culture with other social groups. To fulfill this purpose it has to do with direct observation and comparative studies, and then the information has been processed through statistical and comparative charts and graphs. This entails defining the textiles of the Casma culture of the El Campanario Archaeological Complex as the synthesis of a long process of evolution and interaction in the Late Intermediate, the period in which social interactions with their peers of the sierra are still maintained. and the coast Deriving thus in the creation of a cultural syncretism in the valley of Huarmey during the Late Intermediate, where local technical knowledge is combined with the cultural and technological techniques of external social groups. This new knowledge is reflected in the use of the fibers of the camelid hair, the yarn with the "Z" torsion and the characteristic use of the Interwoven Tapestry technique that is used in combination with the local traditions of the use of the cotton, the Yarn with torsion in "S", as well as the elaboration of work garments through the manufacturing technique Tapestry Slotted.